Expression of human adenosine deaminase in mice reconstituted with retrovirus-transduced hematopoietic stem cells. - Wilson, J M (1990)
Recombinant retroviruses encoding human adenosine deaminase (ADA; adenosine aminohydrolase, EC 3.5.4.4) have been used to infect murine hematopoietic stem cells. In bone marrow transplant recipients reconstituted with the genetically modified cells, human ADA was detected in peripheral blood mononuclear cells of the recipients for at least 6 months after transplantation. In animals analyzed in detail 4 months after transplantation, human ADA and proviral sequences were detected in all hematopoietic lineages; in several cases, human ADA activity exceeded the endogenous activity. These studies demonstrate the feasibility of introducing a functional human ADA gene into hematopoietic stem cells and obtaining expression in multiple hematopoietic lineages long after transplantation. This approach should be helpful in designing effective gene therapies for severe combined immunodeficiency syndromes in humans.